2017
DOI: 10.4236/oalib.1103857
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Nursing Students towards Individuals with Mental Illness before Doing the Mental Health Nursing Course

Abstract: The aim of this study was to examine the undergraduate nursing students' attitudes toward individuals with mental illness. Furthermore, it was important to study the perception, attitude, of our students regarding mental illness, which will help in improving the care given to the mentally ill in the hospitals or in the community. A total of 110 undergraduate students were selected using the stratified random method. Data for the study were collected through the use of a questionnaire. The data were coded and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 49 publications
(36 reference statements)
3
3
0
Order By: Relevance
“…The odds of having negative attitude among nurses with poor knowledge about mental illness were 2.83 times higher as compared to nurses with good knowledge. This aligns with the findings in the WHO report and a study conducted in Sweden [8, 29] which could be explained by lack of adequate training and less supervision by mental health teams as a cause of lack of knowledge. Accordingly, it might be argued that increased level of training have the effect of bringing about a decrease in negative attitude among nurses concerning people with mental disorders and this would reinforce the impression that increased level of knowledge about mental illness has a direct bearing on attitude development among the nurses [30].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The odds of having negative attitude among nurses with poor knowledge about mental illness were 2.83 times higher as compared to nurses with good knowledge. This aligns with the findings in the WHO report and a study conducted in Sweden [8, 29] which could be explained by lack of adequate training and less supervision by mental health teams as a cause of lack of knowledge. Accordingly, it might be argued that increased level of training have the effect of bringing about a decrease in negative attitude among nurses concerning people with mental disorders and this would reinforce the impression that increased level of knowledge about mental illness has a direct bearing on attitude development among the nurses [30].…”
Section: Discussionsupporting
confidence: 91%
“…There were reports of stigmatizing behaviors from health care workers towards patients with SMD which includes offering discouraging advice, negative remarks, rejecting behavior, and negative attitudes [6, 7]. Taking this in account, the attitudes and knowledge of nurses on mental illness have been argued to be a major determinant of the quality and inclusive care for people with mental illness [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, significant disparities were observed in specific questionnaire items, such as Q22 from the BMI questionnaire, indicating that students exposed to the psychiatry course were more inclined to work with and trust mentally ill colleagues compared to their counterparts who did not take the course. This finding resonates with Pusey-Murray's study [20] on Jamaican nursing students, which found that a considerable percentage of participants were uncomfortable working with mentally ill colleagues, highlighting the pervasive stigma associated with mental health issues. However, contrary to prior research indicating significant attitude shifts towards mental illness across different academic years, the current study found no significant relationship between negative views frequency and exposure to the psychiatry course.…”
Section: Discussionsupporting
confidence: 70%
“…There have been allegations of health professionals stigmatizing people with severe mental disorders (SMD), through delivering words of discouragement, making negative statements, rejecting behavior, and having negative attitudes ( 12 , 13 ). Given this stigmatiztion, it has been suggested that the mental health literacy of healthcare professionals on depression is a significant driver of the quality and inclusiveness of care for those with depressive disorders ( 14 ).…”
Section: Introductionmentioning
confidence: 99%